Réponses

2013-04-18T17:41:21+02:00


-12+2x=-5x+2
2x+5x=+2+12
7x=14
x=14/7=2

l'equation est vrai pour  x=2

 

j'avais pas tout ne pas tenir compte

 



 -12 + 2 x = - 5 x + 2 2 ( y – 7) – ( 3 y + 11 ) = 5 – ( 2 y – 5 )

5-2y +5= 10-2y

-12+2x=10-2y
2x=22-2y

x=(22-2y)/2=11-y


-5(11-y) +22(y-7)-3y-11=5-2y+5
-55+5y+22y-154-3y-11=10-2y

5y+22y-3y+2y=10+55+154+11
26y=230

y=230/26=115/13
donc

x=11-(115/13)=((11*13)-115)/13=28/13

 

sauf erreur de ma part

2013-04-18T17:59:10+02:00

-12+2x=-5+2

-12-2=-5x-2x

-14=-7x

x=-14/7=2

 

2(y-7)-(3y+11)=5-(2y-2)

2y-14-3y-11=5-2y+5

-y-14=10-2y

-14-10=-2y-y

-24=-y

y=24